Exploring Interactive Typography as a Visual Communication Medium to Enhance Generation Z Engagement on Digital Platforms - Farah Fadira (Pixel :Jurnal Ilmiah Komputer Grafis, 2025)
The research examined interactive text as a possible interactive form of pictorial communication for generation z meaningfully engaging on online platforms. By adopting a three-phase methodology towards design, realización and evaluation, the research examines how much movement, responsiveness and user interactivity influences the interpretation of the the communicative message and the emotional. The research uses an interweaving of methodologies. Methodology usability testing, engagement analytics and qualitative indicators, which indicate kinetic text, format variations, and animation responsive were more interesting, easier to understand, and shareable than static texts. Findings suggest participants read as a participant and active, as opposed to passive, which wasn't related to their use of interactions. At last the results deliver positioning for interactive text read as a new thinking strategies for the needs of generation z for authenticity and enable discourse regarding potential opportunities for augmented reality and artificial intelligence-enabled personalization